The Economics of Natural Disasters : Concepts and Methods - Hallegatte, Stephane; Przyluski, Valentin (2012)
Large-scale disasters regularly affect societies over the globe, causing large destruction and damage. After each of these events, media, insurance companies, and international institu-tions publish numerous assessments of the "cost of the disaster." However these assessments are based on different methodologies and approaches, and they often reach different results. Besides methodological differences, these discrepancies are due to the multi-dimensionality in disaster impacts and their large redistributive effects, which make it unclear what is included in the estimates. But most importantly, the purpose of these assessments is rarely specified, although different purposes correspond to different perimeters of analysis and different definitions of what a cost is. To clarify this situation, this paper proposes a definition of the cost of a disaster, and emphasizes the most important mechanisms that explain and determine this cost. It does so by first explaining why the direct economic cost, that is, the value of what has been damaged or destroyed by the disaster, is not a sufficient indicator of disaster seriousness and why estimating indirect losses is crucial to assess the consequences on welfare. The paper describes the main indirect consequences of a disaster and the following reconstruction phase, and discusses the economic mechanisms at play. It proposes a review of available methodologies to assess indirect economic consequences, illustrated with examples from the literature. Finally, it highlights the need for a better understanding of the economics of natural disasters and suggests a few promising areas for research on this topic.